1999
DOI: 10.1289/ehp.99107879
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls and methylmercury act synergistically to reduce rat brain dopamine content in vitro.

Abstract: Consumption of contaminated Great 1Las fish by pregnant women is associated with decreased birth weight and deficits in cognitive function in their infants and children. These fish contain many known and suspected anthropogenic neurotoxicants, makdig it difficult to determine which contaminant(s) are responsible for the observed deficits. We have undertaken a series of experiments to determine the relevant toxicants by comparing the neurotouic efifect of two of these contaminants-polychorinated biphenyls (PCBs) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(54 citation statements)
references
References 31 publications
6
48
0
Order By: Relevance
“…The elevations in dialysate DA concentrations seen here are strikingly similar to those seen in media DA concentrations after acute ex vivo exposure of adult rat striatal tissue to Aroclor mixtures (Bemis and Seegal 1999;Chishti et al 1996) and are likely to reflect similar mechanisms. Indeed, in those reports, we suggested that the elevations in media DA may have been due to PCB-induced inhibition of DA transporters.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The elevations in dialysate DA concentrations seen here are strikingly similar to those seen in media DA concentrations after acute ex vivo exposure of adult rat striatal tissue to Aroclor mixtures (Bemis and Seegal 1999;Chishti et al 1996) and are likely to reflect similar mechanisms. Indeed, in those reports, we suggested that the elevations in media DA may have been due to PCB-induced inhibition of DA transporters.…”
Section: Discussionsupporting
confidence: 74%
“…Using pheochromocytoma (PC12) cells, we demonstrated that only noncoplanar PCB congeners significantly decreased cell DA content (Shain et al 1991). Similar decreases in tissue DA content were described by Chishti et al (1996) and by Bemis and Seegal (1999) after ex vivo exposure of striatal slices from adult rats to commercial mixtures of PCBs. These decreases in tissue DA content after acute exposure were accompanied by significant elevations in media DA, which led us to suggest that PCBs either enhance release of DA and/or inhibit transport of the neurotransmitter back into the neuron.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…However, adverse developmental effects of MeHg associated with seafood consumption have not been observed consistently (22,25) . Some evidence suggests PCB, which have been measured at fairly high concentrations in samples of seafood from Spain, may potentiate adverse developmental effects of MeHg (11,(49)(50)(51)(52) . It has also been suggested that adverse neurodevelopmental effects of PCB may be lower in breast-fed children (38) .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional cut at the level of the hypothalamus was made and the rostral portion was placed in ice-cold HBHS. Several 350-μM thick slices containing the striatum were collected, processed, and prepared for Mn exposure according to Chishti et al (1996) and Bemis and Seegal (1999). In all cases, striatal slices were incubated in 24-well plates containing 500 μl of 1% HBHS/well and the indicated working concentrations of Mn.…”
Section: Striatal Tissue Experimentsmentioning
confidence: 99%